Authentic TikTok Storytelling Builds Personal Brands for Indonesian Food and Beverage SMEs - Rosiana Alim; Christina Whidya Utami; Burhan Bungin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rise of TikTok as a platform for authentic, engaging content has transformed digital marketing, particularly for small and medium enterprises in Indonesia’s food and beverage sector. This study explores how these business owners use TikTok to establish themselves as micro-celebrities, fostering audience connections through fun, relatable content. The research aims to understand how storytelling and platform features enhance brand awareness and loyalty. Using an ethnographic approach, data were collected through in-depth interviews with four food and beverage business owners and visual observations of their TikTok videos, focusing on accounts with significant followings. The findings reveal that authentic narratives, such as daily business activities or personal struggles, create emotional bonds with audiences, driving engagement through comments, shares, and live interactions. Unlike other platforms prioritizing aesthetics, TikTok’s emphasis on raw content empowers these owners to build personal brands cost-effectively. However, the small sample limits generalizability to other sectors. This study concludes that TikTok offers a powerful, accessible marketing tool for small businesses, enabling owners to become relatable figures who connect with audiences, ultimately enhancing brand visibility and customer loyalty in Indonesia’s competitive market.